تحسين خواص الفولاذ المنخفض الكربون باستخدام المعالجة المزدوجة (كربنة غازية+كرمنة صلبة) - نبيل مقدسي; خليل عزيمة; معن معلا (Tishreen University, 2019)
تعتبر عملية الكرمنة إحدى تقنيات المعالجة السطحية التي يتم بموجبها إنتاج طبقات على سطح الفولاذ تتمتع بالقساوة العالية وبالمقاومة الجيدة للتآكل والاهتراء. تهدف هذه الدراسة إلى تحسين الخواص الميكانيكية ورفع مقاومة التآكل والاهتراء لأحد أنواع الفولاذ المنخفض الكربون المحتوي على 0.15%C المستخدم محلياً في تصنيع بعض عناصر الآلات. حيث تم تطبيق الكرمنة الصلبة عند الدرجة 1000C0 لمدة (2-4-6)  ساعة على الترتيب. إن عمق الطبقة المتشكلة على سطح الفولاذ يزداد بازدياد زمن المعالجة ونسبة كلوريد الأمونيوم في خليط الكرمنة. أظهر البحث أهمية نسبة الكربون في العينات المعالجة , إن زيادة نسبة الكربون على السطح لها دور مهمّ في تحسن الخواص الميكانيكية ومقاومة الفولاذ للتآكل والاهتراء. حيث لوحظ أن المعالجة المزدوجة (الكربنة تليها الكرمنة) أدت إلى تحسين متانة الشد بنسبة 12%, وإلى ازدياد قساوة السطح بمقدار 7 مرات وتحسين مقاومة الفولاذ للتآكل. The chromizing process is one of the surface treatment technologies that can produce chromium containing surface layers with high hardness, good corrosion, and wear resistance on the steel matrix. This study aims to improve the mechanical properties and increase corrosion and wear resistance on one of low carbon steel containing 0.15%C locally used in manufacturing some of machine elements. Pack chromizing process was applied at 1000 0C for 2, 4, and 6 h respectively. The depth of coated layer on the surface increases by increasing the coating time and the ratio of Ammonium Chloride in the chromizing mixture. This study showed the importance of carbon content on the treated samples. The increase of carbon content on the surface has an important effect in improving the mechanical properties and increasing corrosion and wear resistance. It was observed that the dual treatment (carburizing followed by chromizing) increased the tensile strength, surface hardness, and corrosion resistance.